PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS VII SMP NEGERI 11 KOTA BENGKULU - jayanti, meli dwi; maizora, syafdi; Yensy B, Nurul Astuty (JP2MS, 2018)
The aim of this research was to improve Students’ learning score through application of learning model of Think Talk Write in seven grade of junior high school number eleven in Bengkulu city. This research was a classroom action research. The subject of this research was students of VIIB Class in junior high school number eleven in Bengkulu city which number 28 Students. The instrument of this research was students’ learning scores. Learning score could be improved by making students’ working paper with simple questions and steps so that the student would be able to understand the material easier and motivating students to study harder in doing Think Talk Write to achieve the completeness score. Enhancement students score could be seen on increasing of the students’ average scores from cycle I until cycle III, they were 67,9; 73,9; 86,6 with percentages of completeness of learning score from cycle I until cycle III were 35,71%; 60,71%; 89,29%.Key words: Think Talk Write; students’ learning scores